2008
DOI: 10.1016/j.clim.2008.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent detection of secreted products from human lymphocytes by microengraving: Cytokines and antigen-reactive antibodies

Abstract: Cell surface determinants, cytokines and antibodies secreted by hematopoietic cells are used to classify their lineage and function. Currently available techniques are unable to elucidate multiple secreted proteins while also assigning phenotypic surface-displayed markers to the individual living cells. Here, a soft lithographic method, microengraving, was adapted for the multiplexed interrogation of populations of individual human peripheral blood mononuclear cells for secreted cytokines (IFN-γ and IL-6), ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 33 publications
0
63
0
Order By: Relevance
“…The arrangement of captured antibodies on the resulting microarray matches the arrangement of cells in the microwells. This printing process can be repeated with the same set of cells to produce multiple replicate antibody microarrays [supporting information (SI) Scheme S1a] (11,12).…”
Section: Resultsmentioning
confidence: 99%
“…The arrangement of captured antibodies on the resulting microarray matches the arrangement of cells in the microwells. This printing process can be repeated with the same set of cells to produce multiple replicate antibody microarrays [supporting information (SI) Scheme S1a] (11,12).…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of a direct assay to measure both functions (cytolysis and secretion), it has remained unclear to what extent cells exhibit both responses concurrently when encountering an APC. We have previously shown that the elastomeric array of microwells used here can also detect the frequencies and rates of secretion of multiple cytokines by a process called microengraving (26,27). According to this method, a glass slide coated with antibodies specific for .…”
Section: Detection Of Hiv-specific Cytotoxic Effector T Cells From CLmentioning
confidence: 99%
“…In the earlier mentioned human T1D study, an insulin-specific, PLN-isolated T cell clone was not found in the autologous spleen (21), suggesting that no expansion or retention of insulin-specific T cells was taking place. In contrast, autoreactive B cells from mouse and human diabetic pancreas infiltrates have been identified in the spleen of NOD mice and blood of diabetic patients, respectively (27,28). B cells have been shown to be efficient autoantigen-specific APCs in the PLNs and the spleen of NOD mice, as they express high levels of costimulatory molecules (29,30).…”
Section: T Ype 1 Diabetes (T1d) Is An Autoimmune Disease Defined By Tmentioning
confidence: 99%